2014
DOI: 10.1002/tox.21992
|View full text |Cite
|
Sign up to set email alerts
|

Latex ofEuphorbia antiquorum-induced S-phase arrest via active ATM kinase and MAPK pathways in human cervical cancer HeLa cells

Abstract: Latex of Euphorbia antiquorum (EA) has demonstrated great chemotherapeutic potential for cancer. However, the mechanisms of anti-proliferation of EA on cancer cell remain to be further investigated. The purpose of this study was to explore the influence of EA in human cervical cancer cells. Here, the cell cycle distribution by flow cytometry was examined and the protein expression by the western blotting methods was analyzed. From the cytometric results it was shown that EA-induced S-phase arrest in a concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Overexpression of miR-424 inhibited the expression of CHEK1 and p-CHEK1 at residue Ser345, and decreased the activity of the luciferase-reporter containing the 3′-untranslated region of CHEK1. Hsieh et al ( 40 ) revealed that Euphorbia antiquorum extracts could downregulate topoisomerase and activate ATM kinase, inducing the CHEK1 / 2 and mitogen activated protein kinase signaling pathways, and promoting the degradation of cell division cycle 25A to induce S-phase arrest in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-424 inhibited the expression of CHEK1 and p-CHEK1 at residue Ser345, and decreased the activity of the luciferase-reporter containing the 3′-untranslated region of CHEK1. Hsieh et al ( 40 ) revealed that Euphorbia antiquorum extracts could downregulate topoisomerase and activate ATM kinase, inducing the CHEK1 / 2 and mitogen activated protein kinase signaling pathways, and promoting the degradation of cell division cycle 25A to induce S-phase arrest in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are involved in many aspects of the control of cellular proliferation and apoptosis and have been implicated in the regulation of gene expression in the ER stress signaling cascade in cervical cancer [24, 25]. We performed Western blotting to analyze MAPK signaling pathways induced by PD in cervical cancer cells, and found that PD induced apoptosis through activation of JNK and p38 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data agree with Carroll and Marshak (1989), they found a higher CK2 activity in S phase cells than that in quiescent cells in WI38 human lung fibroblasts. The increase in S phase was reported to be related to ATM, which is a CK2 phosphorylation substrate, activation (Hsieh et al 2015;Lee et al 2018), indicating the increase in CK2 activity after IR is related to the DNA damage repair process. Almost all eukaryotic cells showed an increase in G2/M phase after radiation (Xu B et al 2002).…”
Section: Discussionmentioning
confidence: 99%